2014
DOI: 10.1007/s11743-014-1589-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonionic Rosin Surfactants on Surface Activity of Silica Particles and Stability of Oil in Water Emulsions

Abstract: Rosin as a natural product has become a source for production of less toxic bio‐surfactants to produce emulsions which are widely used in various agriculture and food products, cosmetic, and pharmaceutical industries. In this respect, a nonionic surfactant was prepared from reaction of rosin acids and rosin maleic anhydride adduct with poly(ethylene glycol) monomethyl ether 750 (MPEG 750) to produce a rosin ester (RMPEG 750). The surface activity parameters of the prepared surfactants, such as surface excess c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For this reason, ionic liquids have been used as solvent and capping agent to activate the surface properties of silica to remove water pollutants [27]. In our previous work, the silica nanoparticles were activated with bio-based surfactants, based on rosin, to enhance their surface activity [28]. In this respect, nanogels based on ionic and nonionic monomers were selected to coat the silica surfaces to prepare novel water-based amphiphilic silica nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, ionic liquids have been used as solvent and capping agent to activate the surface properties of silica to remove water pollutants [27]. In our previous work, the silica nanoparticles were activated with bio-based surfactants, based on rosin, to enhance their surface activity [28]. In this respect, nanogels based on ionic and nonionic monomers were selected to coat the silica surfaces to prepare novel water-based amphiphilic silica nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous work [28], the surface activity of silica was modified by using nonionic surfactants and the water surface tension was reduced from 72.1 mN/m to 32 mN/m due to adsorption of surfactants on the silica nanoparticles. In the present work, surface of silica nanoparticles was modified with ionic and nonionic nanogels to reduce the water surface tension to facilitate the diffusion of organic or inorganic pollutants from water to the silica-nanogel composites.…”
Section: Surface Activity and Contact Angle Of Silica-nanogel Compositesmentioning
confidence: 99%
“…Both electrostatic forces and hydrophobic effect can mediate surfactant-nanoparticles interactions. A survey of the literature revealed that the balance between the two mechanisms depends strongly on the particle charge and the nature of surfactant head group [38][39][40][41][42]. In the case of like charged partners, hydrophobic effects prevail, whereas, when oppositely charged nanoparticles and surfactants interact, electrostatic forces play a key role.…”
Section: Resultsmentioning
confidence: 99%
“…2596) were synthesized as described in the previous work [39,40]. The compunds were of high purity as these were recrystallize many times and the FTIR and NMR spectra along with surface tension measuremets suggest that the compounds were free from any impurity [41][42][43][44]. The chemical structures and scheme of synthesis of all three surfactants is illustrated in the Fig.…”
Section: Methodsmentioning
confidence: 99%